Efficacy of metformin and insulin in the management of gestational diabetes mellitus: A comparative study - Anupama Marnal B. A; Virupaksha Ajjammanavar; Sumuk M. S.; Mamatha S.; Jayashree S; Poornima M (Journal of Krishna Institute of Medical Sciences University, 2023)
Background: In Gestational Diabetes Mellitus (GDM), the insulin secretion is not adequate enough to compensate for the severity of hyperglycaemia and pregnancy is also a state of high insulin resistance which leads to ineffective glycaemic control. Aim and Objectives: To compare the efficacy of metformin and insulin in management of GDM; and to assess neonatal and maternal outcomes in the study group. Material and Methods: One hundred pregnant women visiting the Outpatient Department of Obstetrics and Gynecology, JSS Hospital, Mysuru were screened for GDM at first antenatal visit. If the first test results were negative, then second test was done at 24 - 28 weeks of gestation. One hundred pregnant women diagnosed as GDM after 20 weeks of gestation by Diabetes in Pregnancy Study Group of India (DIPSI) method were included for the study. They were randomly assigned into two groups with 50 patients each and were subjected to pharmacological treatment with either insulin or metformin. Optimum glycemic control between the two groups was studied along with the maternal and fetal outcome. Results: Our study showed no significant difference in GDM with the use of metformin or insulin. All patients (100%) from the insulin group achieved good glycemic control whereas in the metformin group, 98% achieved good glycemic control. Maternal and fetal outcomes were also not significant between the two groups. Conclusion: Our study showed no significant difference in the use of metformin or insulin and suggests that metformin is effective in controlling GDM without associated higher risk of maternal or neonatal complications compared with insulin.